2021
DOI: 10.3389/fcimb.2021.586392
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gut Microbiota on Radiation-Induced Enteritis

Abstract: Radiotherapy is an important treatment for abdominal tumors. A critical side effect for this therapy is enteritis. In this review, we aim to summarize recent findings in radiation enteritis, in particular the role of gut microbiota dysbiosis in the development and therapy of the disease. Gut microbiota dysbiosis plays an important role in the occurrence of various diseases, such as radiation enteritis. Abdominal radiation results in changes in the composition of microbiota and reduces its diversity, which is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 97 publications
1
54
0
Order By: Relevance
“…Our study as well as other studies reported dysbiosis in the gut microbiota following abdominal or total body irradiation, characterized by a decrease in the diversity of gut microbiota with a less relative abundance of beneficial bacteria, and an increase in the relative abundance of opportunistic pathogens ( 15 , 16 ). Radioprotection based on gut microbiota, such as probiotics, fecal microbiota transplantation and intervention with active compounds, can regulate gut microbiota balance and alleviate RIII in the irradiated animals and patients subjected to radiotherapy to some extent ( 15 , 17 19 ).…”
Section: Introductionsupporting
confidence: 83%
“…Our study as well as other studies reported dysbiosis in the gut microbiota following abdominal or total body irradiation, characterized by a decrease in the diversity of gut microbiota with a less relative abundance of beneficial bacteria, and an increase in the relative abundance of opportunistic pathogens ( 15 , 16 ). Radioprotection based on gut microbiota, such as probiotics, fecal microbiota transplantation and intervention with active compounds, can regulate gut microbiota balance and alleviate RIII in the irradiated animals and patients subjected to radiotherapy to some extent ( 15 , 17 19 ).…”
Section: Introductionsupporting
confidence: 83%
“…Cancer patients exposed to radiation therapy exhibit marked alterations in gut microbiota composition, with a decrease in protecting Bifidobacterium and Lactobacillus spp. together with an excessive growth of Gram-negative pathogen bacilli [ 238 ]. Maintenance of normal microbiota using probiotics exerts nutrient competition and avoids binding of intestinal pathogens to host mucosa, thus preventing bacterial translocation.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Katz et al found a large number of periodontal pathogens- Porphyromonas gingivalis ( P. gingivalis ) in gingival squamous cell carcinoma (GSCC) tissues ( Katz et al, 2011 ; Ritter and Greten, 2019 ), in which microorganism-mediated chronic inflammation plays a role in promoting disease progression ( Bhatt et al, 2017 ). Recent studies on mice and humans have shown that gut microbiome modulates the anti-tumor efficacy in chemotherapy and immunotherapy by shaping host immunity ( Iida et al, 2013 ; Gopalakrishnan et al, 2018 ; Matson et al, 2018 ; Routy et al, 2018 ; Tanoue et al, 2019 ; Jian et al, 2021 ). Compared with the untreated group, cancer patients treated with antibiotics had a lower response to anti-PD-1 immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Restructure of sterile mice with feces from anti-PD-1 responding patients improves tumor control and T cell responses ( Routy et al, 2018 ). The intestinal microbiota regulates dendritic cells and CD4 + T cells to enhance cancer immune surveillance and advance therapeutic effects ( Iida et al, 2013 ; Vétizou et al, 2015 ; Gopalakrishnan et al, 2018 ; Matson et al, 2018 ; Routy et al, 2018 ; Tanoue et al, 2019 ; Jian et al, 2021 ). However, it is still not fully understood how the oral microbiota changes and whether the oral microbiota could regulate the tumor-infiltrating CD8 + T cell responses in OPC.…”
Section: Introductionmentioning
confidence: 99%